2019
DOI: 10.1038/s41467-019-08940-5
|View full text |Cite
|
Sign up to set email alerts
|

Subtle changes in chromatin loop contact propensity are associated with differential gene regulation and expression

Abstract: While genetic variation at chromatin loops is relevant for human disease, the relationships between contact propensity (the probability that loci at loops physically interact), genetics, and gene regulation are unclear. We quantitatively interrogate these relationships by comparing Hi-C and molecular phenotype data across cell types and haplotypes. While chromatin loops consistently form across different cell types, they have subtle quantitative differences in contact frequency that are associated with larger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 79 publications
14
125
0
Order By: Relevance
“…4b,c) revealed how relatively small changes in both ATAC-seq and CHi-C intensity (~2 fold change) correlated with larger changes in expression (~5 fold change). This is consistent with similar patterns observed in different cell types 17 .…”
Section: Correlating Chromatin Dynamics With Gene Expressionsupporting
confidence: 93%
See 1 more Smart Citation
“…4b,c) revealed how relatively small changes in both ATAC-seq and CHi-C intensity (~2 fold change) correlated with larger changes in expression (~5 fold change). This is consistent with similar patterns observed in different cell types 17 .…”
Section: Correlating Chromatin Dynamics With Gene Expressionsupporting
confidence: 93%
“…We next went on to test whether these dynamic measures of DNA activity, interaction and expression exhibited any correlation between their time course profiles. Previous studies, using measurements of H3K27ac, Hi-C and expression across different cell types, demonstrated how subtle changes in contact frequency correlated with larger changes in active DNA and expression 17 . We wanted to determine the nature of this relationship in our data, from a single, activated cell type.…”
Section: Correlating Chromatin Dynamics With Gene Expressionmentioning
confidence: 99%
“…Given the large size of some SVs and STRs, it has been hypothesized that these variants may affect gene expression by altering chromatin structure and affecting enhancer-promoter interactions Duggal et al, 2014;Greenwald et al, 2019;Schoenfelder et al, 2015). We used promoter capture Hi-C data to characterize whether distal SV/STR eQTLs localize near gene promoters and found that SVs of all classes and STRs overlapping or close to distal loop anchors are strongly enriched for being eQTLs for the gene they loop to.…”
Section: Discussionmentioning
confidence: 99%
“…Since chromatin looping has been shown to play a key role in the regulation of genes by positioning regulatory regions near gene promoters (Duggal et al, 2014;Greenwald et al, 2019;Rao et al, 2015;Schoenfelder et al, 2015), we sought to determine whether distal eVariants are located near the promoters of their eGenes in three-dimensional space due to chromatin looping. We obtained chromatin loop calls from iPSC promoter capture Hi-C data (Montefiori et al, 2018a) that define promoter loops between gene promoters (promoter anchors) and distal sequences (distal anchors, Figure 5A).…”
Section: Multi-egene Eqtls Colocalize With Distal Chromatin Loop Anchorsmentioning
confidence: 99%
“…However, Sim3C imposes strong assumptions to parametrically mimic Hi-C contact matrix structures and arbitrarily introduces random domain structures, e.g., topological associating domains (TADs). The properties of actual chromatin interactions at dif-ferent scales 11,[21][22][23] are far more nuanced than the basic factors that Sim3C takes into account. Consequently, the resulting Sim3C simulated contact matrices do not visually resemble biological Hi-C contact matrices (Fig.…”
Section: Introductionmentioning
confidence: 99%